The Role of Case-Based Learning in Developing Students' Critical Thinking of Chinese Language Study Program - Ita Sarmita Samad; Mir'ah Azizah; Nur Nasharuddin Noni (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to examine the extent to which Case-Based Learning (CBL) plays a role in developing critical thinking skills of students of the Chinese Language Education Study Program. Critical thinking skills are seen as one of the main competencies in 21st-century higher education, especially in foreign language learning which requires students not only to master linguistic aspects, but also to understand the socio-cultural context. This study used a quasi-experimental design with a non-equivalent control group pattern involving 40 students in the odd semester of 2024/2025, consisting of 20 experimental group students taught with CBL and 20 control group students taught by conventional methods in the form of lectures and practice questions. The research instrument is in the form of a critical thinking essay test based on the California Critical Thinking Skills Test (CCTST) indicator, which is validated by experts and tested for reliability. Pretest and posttest results data were analyzed using normalized gain (N-gain) scores to assess learning effectiveness. The results showed that the experimental group obtained an average N-gain of 0.763 (high category) with a range of 0.54–1.00, while the control group only achieved an average N-gain of 0.45 (medium category) with a range of 0.23–0.80. These differences in achievement confirm that CBL is more effective than conventional methods in improving students' ability to analyze, evaluate, and interpret. Thus, it can be concluded that the application of CBL makes a significant contribution to the development of students' critical thinking skills, as it encourages them to connect theory with practice through authentic case analysis. These findings recommend that CBL be systematically integrated into the Chinese language learning curriculum to produce graduates who are critical, reflective and adaptive in the face of global challenges.